A Critical Analysis of the Relationship Between Visioning and Digital Transformation in the Insurance Industry - Malambo, Maalila (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This critique assesses "The Effect of Visioning on Digital Transformation in the Insurance Industry" by Chiguvi, Zaranyika, Marozwa, and Dube (2023), focusing on its objectives, methodology, findings, and conclusions. It highlights the importance of visioning in digital transformation within the insurance sector and evaluates the study's research framing, literature review, methodology, findings, and discussions. Design/methodology/approach: The study employs a positivist research philosophy and a quantitative approach, utilizing quota sampling to gather data from employees and senior management in the Zimbabwean insurance industry. Findings: The findings indicate a significant positive relationship between visioning and digital transformation, consistent with previous research. Research limitations/implications: The study's limitations include the absence of explicitly stated research questions, identified gaps, and detailed sampling procedures, which may impact transparency and framing. Practical implications: The study underscores the importance of visioning in digital transformation, providing valuable insights for managerial practices in the insurance industry. Originality/value: The critique emphasizes the study's contribution to understanding the role of visioning in facilitating digital transformation in the insurance sector, suggesting that further elaboration with practical examples and future research directions could enhance its academic and practical impact.